Effects of extracellular magnesium extract on the proliferation and differentiation of human osteoblasts and osteoclasts in coculture - Wu, Lili; Feyerabend, Frank; Schilling, Arndt F.; Willumeit-Römer, Regine; Luthringer, Bérengère J.C. (Acta biomaterialia, 2015)
[Display omitted] Coculture of osteoblasts and osteoclasts is a subject of interest in the understanding of how magnesium (Mg)-based implants influence the bone metabolism and remodeling upon degradation. Human telomerase reverse transcriptase (hTERT) transduced mesenchymal stem cells (SCP-1) were first differentiated into osteoblasts with osteogenic supplements and then further cocultured with peripheral blood mononucleated cells (PBMC) without the addition of osteoclastogenesis promoting factors. Concomitantly, the cultures were exposed to variable Mg extract dilutions (0, 30×, 10×, 5×, 3×, 2× and 1×). Phenotype characterization documented that while 2× dilution of Mg extract was extremely toxic to osteoclast monoculture, monocytes in coculture with osteoblasts exhibited a greater tolerance to higher Mg extract concentration. The dense growth of osteoblasts in cultures with 1× dilution of Mg extract suggested that high concentration of Mg extract promoted osteoblast proliferation/differentiation behavior. The results of intracellular alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) activities as well as protein and gene expressions of receptor activator of nuclear factor kappa-B ligand (RANKL), macrophage colony-stimulating factor (M-CSF), and osteoclast-associated receptor (OSCAR) revealed significantly enhanced formation of osteoblasts whereas decreased osteoclastogenesis in the cultures with high concentrations of Mg extract (2× and 1× dilutions). In conclusion, while an increased osteoinductivity has been demonstrated, the impact of potentially decreased osteoclastogenesis around the Mg-based implants should be also taken into account. Cocultures containing both bone-forming osteoblasts and bone-resorbing osteoclasts should be preferentially performed for in vitro cytocompatibility assessment of Mg-based implants as they more closely mimic the in vivo environment. An attractive human osteoblasts and osteoclasts cocultivation regime was developed as an in vitro cytocompatibility model for magnesium implants. Parameters in terms of cellular proliferation and differentiation behaviors were investigated and we conclude that high concentration of magnesium extract could lead to a promotion in osteoblastogenesis but an inhibition in osteoclastogenesis. It could contribute to the repeated observations of enhanced bone growth adjacent to degradable magnesium alloys. More interestingly, it demonstrates that compared to monoculture, osteoclasts in cocultures with osteoblasts exhibited higher tolerance to the culture environment with high magnesium extract. It might attribute to the neutralization process of the alkaline medium by acid generated by increased amount of osteoblasts in the condition with high concentration of Mg extract. The submitted work could be of significant importance to other researchers working in the related field(s), thus appealing to the readership of Acta Biomaterialia.